China and Iran : economic, political, and military relations - Harold, Scott, 1975-; Nader, Alireza (Occasional paper (Rand Corporation) ;, 2012)
Over the past few decades, China and Iran have developed a broad and deep partnership centered on China's energy needs and Iran's abundant resources as well as significant non-energy economic ties, arms sales and defense cooperation, and geostrategic balancing against the United States. This partnership presents a unique challenge to U.S. interests and objectives. In particular, China's policies have hampered U.S. and international efforts to dissuade Iran from developing a nuclear weapons capability. This paper examines factors driving Chinese-Iranian cooperation, potential tensions in the Chinese-Iranian partnership, and U.S. policy options for influencing this partnership to meet U.S. objectives. The authors conclude that the U.S. ability to fundamentally reshape China's relationship with Iran is fairly limited, but that the United States should continue to forestall an Iranian nuclear weapons capability and pressure China to reduce ties to Iran.